Concrete5 Beginner's Guide. - Laubacher, Remo (Packt Pub., 2011)
This book is part of Packt's Beginner's Guide series. You will be guided through the set up of a Concrete5 site with step-by-step practical examples. This book is ideal for developers who would like to build their first site with Concrete5. Some k.